Artificial intelligence (AI) technology in OpenAI ChatGPT application: A review of ChatGPT in writing English essay (ELT Forum: Journal of English Language Teaching, 2023)
ChatGPT is a product of AI that is currently being widely discussed on Twitter. This research reviews how ChatGPT writes English essays. This research is descriptive qualitative. The analysis shows that we can access ChatGPT on openai.com or chat.openai.com on the browser. If we do not have an account, we register via email, Google, or Microsoft account. After login, enter a question or statement in the conversation column provided. Send it and ChatGPT will respond and the answer appear quickly. The researcher tries ChatGPT “Can you help me in doing my English assignment?", and the ChatBot replies "Of course! I'd be happy to help you with your English assignment. What do you need help with? Do you have a specific question or task that you're working on, or is there a broader topic that you'd like help with? It would be helpful to have some more information so that I can better understand how I can assist you". Based on several tries, ChatGPT can answer all questions on various topics such as English essays including a descriptive text about Solo and My Family, recount text about personal experience and unforgettable moments, resolution in 2023, and future career. ChatGPT considers the event orders and writing order, including using main, explanatory sentences, and a conclusion. It uses two voices both active and passive voice. Besides, it considers tenses use related to the given topic essay. However, from examples of English essays produced by ChatGPT, it certainly requires further research to find out that the essay results are grammatically accurate.